Bile secretory immunoglobulin A in biliary infection and cholelithiasis - Yio, X Y; Jin, B W; Yin, F Z; Li, X J (Gastroenterology (New York, N.Y. 1943), 1992)
Bile samples from 71 patients with cholelithiasis and a control group of 10 subjects without hepatobiliary diseases were cultured for bacteria and measured for secretory immunoglobulin A (SIgA) using enzyme immunoassay specific for SIgA. The results of bile bacterial culture were all positive in patients with primary bile duct pigment stones, and significantly lower bile SIgA levels were observed than in normal controls (P less than 0.005). It was also shown that the constitutent ratios of SIgA to total bile immunoglobulin and the bile-serum ratio of SIgA were markedly lower in these patients than in normal controls (P less than 0.001, P less than 0.001). In patients with cholecystolithiasis, bile SIgA concentrations of patients with biliary infections were remarkably lower than those of patients without biliary infection (P less than 0.01) and those of normal controls (P less than 0.01). These results suggest a close relationship between biliary tract infection and low concentrations of bile SIgA.